Rotation-tolerant representations elucidate the time-course of high-level object processing - Denise Moerel; Tijl Grootswagers; Amanda K. Robinson; Patrick Engeler; Alex O. Holcombe; Thomas A. Carlson (PLoS ONE, 2026)
Despite the very different retinal images that result from different viewing conditions, humans have little difficulty recognising visual objects in varying circumstances. One source of variability is 2-D rotation, which results in an object having different orientations. Here, we studied how the brain transforms rotated object images into object representations that are tolerant to rotation. We measured time-varying electroencephalography responses to object images shown in eight different orientations, presented at either 5 Hz or 20 Hz. We used multivariate classification to assess when rotation-tolerant object information emerged, and whether the rotation-tolerant processing would be limited at the faster presentation rate. We compared this to fixed-rotation measures of object decoding, where the classifier is trained and tested on the same orientation. Our results showed that both fixed-rotation and rotation-tolerant object decoding emerged at an early stage of processing, less than 100 ms after stimulus onset. However, rotation-tolerant information peaked later than fixed-rotation information, suggesting rotation-tolerant object representations are most prominent during a late stage of processing, around 200 ms after stimulus onset. Both fixed-rotation and rotation-tolerant object information was lower for the 20 Hz compared to 5 Hz presentation rate, which suggests that object information processing is disrupted, but not eliminated, for fast presentation rates. Our results show that object information arises at similar times in the brain regardless of whether it is investigated with the fixed-rotation or rotation-tolerant object decoding method. An object representation that is tolerant to rotation and generalises across different exemplars of the same object is established in later stages of processing.